Cognitive Aspects of Adults and Older Adults with Hearing Loss, Users or not of Hearing Aids: A Meta-Analysis (Global Journal of Human-Social Science, 2025)
Purpose Evaluate cognitive aspects in adults and older adults with hearing loss who use hearing aids compared to those with hearing loss who do not use hearing aids Research Strategies A systematic search across seven databases and gray literature until May 10 2022 sought studies of individuals aged 18 with hearing loss Selection Criteria Both interventional and observational analytical studies were included without language or publication date restrictions Data Analysis Seven articles were included revealing a correlation between cognitive aspects hearing loss and hearing aid use in adults and older adults Comparisons were made between hearing aid users and non-users using validated cognitive questionnaires Risk of bias assessment was assessed using the Joanna Briggs Institute Critical Assessment Checklist followed by random effects metaanalysis The GRADE tool determined certainty of evidence Results Hearing aid users exhibited improved Mini Mental State Examination MMSE performance MD -1 47 CI95 -2 53 - -0 40 I2 7 21 albeit with low certainty Conclusion While MMSE results indicated possible cognitive benefits for adults and older adults using hearing aids the evidence remains uncertain Developing a comprehensive psychological assessment tool encompassing language memory attention executive functions and socialization is recommended to ensure accurate evaluations of this population s health
Keywords: adults; older adults; hearing loss; hearing aids; cognition; cognitive decline